The bony fishes (Teleostei) caught by industrial trawlers off the Brazilian North coast, with insights into its conservation - Marceniuk, Alexandre Pires; Rotundo, Matheus Marcos; Caires, Rodrigo Antunes; Cordeiro, Ana Patricia Barros; Wosiacki, Wolmar Benjamin; Oliveira, Claudio; Souza-serra, Rayla Roberta Maganhães De; Romão-júnior, João Gomes; Santos, Wagner César Rosa Dos; Reis, Thayson Da Silva; Muniz, Mairink Ribeiro; Cardoso, Gustavo Stabile; et al. (Sociedade Brasileira de Ictiologia, 2019)
ABSTRACT The Brazilian North coast is one of the world’s most important shrimp fishery grounds, with a total area of approximately 223,000 km2. However, the available data on the diversity of fish caught by the region’s industrial trawler fleet are limited to the commercially-valuable species. This lacuna in the data on the region’s marine fish fauna is worrying, both for the management of stocks and the conservation of the local biodiversity. The present study was based on a comprehensive inventory of the teleost fishes captured by the industrial outrigger trawling operations off the North coast of Brazil. This inventory recorded 201 species belonging to 64 families and 20 orders, and revealed a unique fauna, characterized by 17 endemic species, and a mixture of estuarine-dependent and marine species, mainly associated with coral reefs. The Kernel density analysis indicated that the industrial trawling fleet operates within an important ecotone, which encompasses the transition zones of different fish communities found off the Brazilian North coast.

RESUMO A costa Norte do Brasil é um dos pesqueiros de camarão mais importantes do mundo, com uma área total de aproximadamente 223.000 km2. No entanto, dados disponíveis sobre a diversidade de peixes capturados pela frota industrial de arrasto de portas na região são limitados às espécies com valor comercial. Essa lacuna no conhecimento sobre a fauna de peixes marinhos da região é preocupante, tanto para o manejo dos estoques quanto para a conservação da biodiversidade local. O presente estudo é baseado num inventário abrangente dos peixes teleósteos capturados por operações de arrasto de portas da frota industrial que opera na costa Norte do Brasil. Este inventário registrou 201 espécies pertencentes a 64 famílias e 20 ordens, e revelou uma fauna única, caracterizada por 17 espécies endêmicas, e uma mistura de espécies estuarino-dependentes e espécies marinhas, principalmente associadas a recifes de corais. A análise da densidade Kernel indicou que a frota industrial de arrasto de portas opera dentro de um importante ecótono, que abrange uma zona de transição de diferentes comunidades de peixes encontrados na costa Norte do Brasil.
Keywords: Biodiversity; Bycatch; Fishes discarded; Inventory; Marine fish; Outrigger trawling; Biodiversidade; Fauna acompanhante; Inventário; Peixes descartados; Peixes marinhos; Pesca de arrasto de portas